A Phase II Trial of a Histone Deacetylase Inhibitor Panobinostat in Patients With Low-Grade Neuroendocrine Tumors. (3rd June 2016) - Jin, Ning; Lubner, Sam J.; Mulkerin, Daniel L.; Rajguru, Saurabh; Carmichael, Lakeesha; Chen, Herb; Holen, Kyle D.; LoConte, Noelle K.
Abstract : Lessons Learned: Pancreatic neuroendocrine tumors versus carcinoid tumors should be examined separately in clinical trials. Progression-free survival is more clinically relevant as the primary endpoint (rather than response rate) in phase II trials for low-grade neuroendocrine tumors. Background: The most common subtypes of neuroendocrine tumors (NETs) are pancreatic islet cell tumors and carcinoids, which represent only 2% of all gastrointestinal malignancies. Histone deacetylase (HDAC) inhibitors have already been shown to suppress tumor growth and induce apoptosis in various malignancies. In NET cells, HDAC inhibitors have resulted in increased Notch1 expression and subsequent inhibition of growth. We present here a phase II study of the novel HDAC inhibitor panobinostat in patients with low-grade NET. Methods: Adult patients with histologically confirmed, metastatic, low-grade NETs and an Eastern Cooperative Oncology Group (ECOG) performance status of ≤2 were treated with oral panobinostat 20 mg once daily three times per week. Treatment was continued until patients experienced unacceptable toxicities or disease progression. The study was stopped at planned interim analysis based on a Simon two-stage design. Results: Fifteen patients were accrued, and 13 were evaluable for response. No responses were seen, but the stable disease rate was 100%. The median progression-free survival (PFS) was 9.9 months, and the median overall survival was 47.3 months. Fatigue (27%), thrombocytopenia (20%), diarrhea (13%), and nausea (13%) were the most common related grade 3 toxicities. There was one grade 4 thrombocytopenia (7%). These results did not meet the prespecified criteria to open the study to full accrual. Conclusion: The HDAC inhibitor panobinostat has a high stable disease rate and reasonable PFS in low-grade NET, but has a low response rate.